Process evaluation for stressor reduction interventions in sport - Randall, Raymond; Nielsen, Karina; Houdmont, Jonathan (Taylor and Francis, 2018)
Stressor reduction interventions may have the potential to improve the well-being of those involved in sport. Organizational psychologists have used these primary interventions in various performance domains. The authors describe the stressor reduction design and implementation processes, and the contexts in which they occur, that impact on these interventions. The authors then examine how process evaluation methods can be applied during stressor reduction in sport settings. Process evaluation requires the frequent collection of data about intervention experiences and events from multiple sources using a mixed methods approach. The article contains practical recommendations for sport psychologists who implement stressor reduction interventions.